PRELIMINARY MASTER'S DEGREE CURRICULUM. (The Accounting Review, 1957)
The Task Committee on Standards of Accounting Instruction of the American Accounting Association was originated to study present college offerings in accounting, to find out what standards are being followed, and ultimately, to suggest desirable standards of accounting instruction in the U.S. The predecessor committee recommended certain standards for undergraduate accounting curricula in the journal The Accounting Review for January, 1954. The present Committee surveyed the various colleges and universities to ascertain the standards in use. This survey was reported in the January 1956 issue of the journal. The Committee is now undertaking a study of graduate programs in accounting. First a pilot questionnaire was sent to a few schools to discover the problems that would be encountered. It was found that master's programs and doctoral programs would need to be studied separately. Accordingly a questionnaire dealing with the master's program was prepared and circulated to 180 schools. The result of the finding has been provided in this article.